Effective Treatment in Patients with Valvular Heart Disease: Mitral Stenosis Complicated by Arterial Fibrillation - Hujamberdiev Mamazoir Ahmedovich; Tashtemirova Iroda Mahkambaevna; Qosimov Iqboljon Sodiqjon ogli (Genius Publishing Group, 2023)
Valvular heart malady is freely related with Blood vessel fibrillation and more than onethird of patients with Blood vessel fibrillation have a few shape of Valvular heart infection Among patients with extreme Valvular heart infection counting those experiencing surgical and transcatheter aortic or mitral valve intercession, Blood vessel fibrillation is related with less ideal clinical results.
Keywords: mitral stenosis; arterial fibrillation; valvular heart disease